Dissection of gastric cancer heterogeneity for precision oncology. Issue 11 (25th September 2019) - Ho, Shamaine Wei Ting; Tan, Patrick
Abstract: Gastric cancer (GC) remains the fifth most prevalent cancer worldwide and the third leading cause of global cancer mortality. Comprehensive ‐omic studies have unveiled a heterogeneous GC landscape, with considerable molecular diversity both between and within tumors. Given the complex nature of GC, a long‐sought goal includes effective identification of distinct patient subsets with prognostic and/or predictive outcomes to enable tailoring of specific treatments ("precision oncology"). In this review, we highlight various approaches to molecular classification in GC, covering recent genomic, transcriptomic, proteomic and epigenomic features. We pay special attention to the translational significance of classifier systems and examine potential confounding factors which deserve further investigation. In particular, we discuss recent advancements in our knowledge of intra‐subtype, intra‐patient and intra‐tumor heterogeneity, and the pivotal role of the tumor stromal microenvironment. Abstract : Gastric cancer (GC) is a highly heterogeneous disease. This review consolidates the latest developments in the molecular classification of GC, with a keen examination of their translational utility. Furthermore, we pay special attention to the role of tumor heterogeneity and the stromal microenvironment in this era of precision oncology.